PENGARUH METODE PEMBELAJARAN COMPLETE SENTECE TERHADAP KETERAMPILAN MENULIS KALIMAT PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS III SD NEGERI ROMANGLASA KECAMATAN BONTONOMPO KABUPATEN GOWA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low sentence writing skills of third-grade students at Romanglasa Elementary School in Bontonompo District, Gowa Regency, characterized by difficulties in capitalizing letters, punctuation, and constructing coherent and logical sentences. The purpose of this study was to determine the effect of the Complete Sentences learning method on sentence writing skills in Indonesian language subjects. This study used a quantitative approach with an experimental design and a One Group Pre-Test Post-Test. The subjects were 22 third-grade students. Data collection used tests (pre-test and post-test), while statistical analysis was conducted using an independent sample t-test. The results showed an improvement in students' sentence writing skills after implementing the Complete Sentences method. This was demonstrated by the average post-test score of 91.59, which was higher than before the treatment. The results of the hypothesis test showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, thus rejecting H0 and accepting H1. Thus, it can be concluded that the Complete Sentence learning method has a significant impact on improving students' sentence writing skills. This method has proven effective in improving students' ability to construct accurate, coherent, and meaningful sentences and can be an alternative, innovative learning strategy in Indonesian language learning in elementary schools.